2022
DOI: 10.1016/j.envint.2021.106914
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter exposures to potential endocrine disrupting chemicals measured by military-style silicone dog tags

Abstract: Studies suggest that exposure to potential endocrine disrupting chemicals (pEDCs) may contribute to adverse health outcomes, but pEDC exposures among firefighters have not been fully characterized. Previously, we demonstrated the military-style silicone dog tag as a personal passive sampling device for assessing polycyclic aromatic hydrocarbon exposures among structural firefighters. This follow-up analysis examined the pEDC exposures based on department call volume, duty shift, and questionnaire variables. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Further, no guidance exists nor have any thorough reviews been conducted to determine the threshold of detection rate for a chemical to be included in an analysis and imputed. Researchers have used a wide range of thresholds ranging from 20% [22] to 75% [23] of observations detected for a chemical to be included in downstream analyses. At a minimum, researchers should conduct sensitivity analyses to evaluate the effect of chosen threshold on their results.…”
Section: Handling Missing Datamentioning
confidence: 99%
“…Further, no guidance exists nor have any thorough reviews been conducted to determine the threshold of detection rate for a chemical to be included in an analysis and imputed. Researchers have used a wide range of thresholds ranging from 20% [22] to 75% [23] of observations detected for a chemical to be included in downstream analyses. At a minimum, researchers should conduct sensitivity analyses to evaluate the effect of chosen threshold on their results.…”
Section: Handling Missing Datamentioning
confidence: 99%
“…The wearing of silicone tags by their service dogs revealed their exposure to 18 PAH, di-n-butyl, diisobutyl phthalate, guaiacol, and DEET classified as having possible carcinogenic effects [ 173 ]. Poutasse et al [ 174 ] used the silicone devices worn by firefighter service dogs for temporized determinations found that some endocrine-disrupting chemicals (EDC) mainly come from household products and environments, and less from work situations of firefighting.…”
Section: Pets As Sentinels For Microclimate Pollutionmentioning
confidence: 99%
“…Many chemical categories can also fall under the pesticide umbrella: organochlorines, organophosphates, neonicotinoids, pyrethroids, amides, pyrazoles, and more. While not a single chemical category, multiple papers have focused on exposure to endocrine disruptors ( Poutasse et al, 2022 ; Varnell et al, 2021 ; Dixon et al, 2019 ).Two studies have utilized silicone wristbands to measure VOCs and SVOCs that originate from the human cells and skin microflora ( Roodt et al, 2018 ; Wooding et al, 2020 ). There have been a few analytical methods explicitly developed for silicone wristbands.…”
Section: Measuring Chemical Exposure With Personal Silicone Samplersmentioning
confidence: 99%
“…Alternative configurations that have not been directly compared to the standard sampler (i.e., a wristband worn on a wrist) include wristbands worn as air samplers on participants with no dermal contact aside from brooches/lapels ( Aerts et al, 2018 ; Bullock et al, 2020 ; Mendoza-Sanchez et al, 2021 ; Swanson et al, 2018 ; Andersen et al, 2021 ), silicone military-style dog tags worn around the neck ( Poutasse et al, 2022 ; Poutasse et al, 2020 ), and pet tags ( Wise et al, 2020 ; Wise et al, 2021 ; Poutasse et al, 2019 ). Two studies have utilized PDMS tubing to create silicone wristbands and anklets, but these studies were not concerned with environmental chemical exposure ( Roodt et al, 2018 ; Wooding et al, 2020 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 99%